Morphological, Thermal and Electrical Properties of (PEO/PVP)/ Au Nanocomposite Before and After Gamma-Irradiation - Abdelrazek, E.M.; Abdelghany, A.M.; Badr, S.I.; Morsi, M.A. (Journal of Research Updates in Polymer Science, 2017)
Gold nanoparticles (Au NPs) have been successfully biosynthesized by Chenopodium murale (C. murale) leaf extract. Au NPs were incorporated within polyethylene oxide (PEO)/polyvinyl pyrrolidone (PVP) polymer blend by casting method. Scanning electron microscope (SEM), Differential scanning calorimetry (DSC), and DC electrical resistivity were used to investigate the morphological, thermal, and electrical properties of blend/Au nanocomposite before and after gamma-irradiation at different doses (1, 2, 3, 4 and 5 MR).SEM micrographs confirmed the dispersion of Au NPs within the polymeric matrix due to effect of irradiation process. DSC analysis showed that the thermal stability for irradiated samples was improved as compared with pure blend and its nanocomposite. DC measurements revealed nonlinear behavior for electrical resistivity versus temperature. The electrical resistivity values for blend/Au nanocopmosite and its high irradiated samples were less compared to pure blend.